PENGARUH SANDBLASTING DAN ELECTROPOLISHING TERHADAP KEKASARAN PERMUKAAN, KEKERASAN, STRUKTUR MIKRO DAN KETAHANAN KOROSI BAJA TAHAN KARAT AISI 316L - , Ishak; , Dr. Suyitno, S.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Electropolishing is the surface finishing/polishing technique electro chemically and sandblasting is the surface treatment method for improving the mechanical properties of the material. In this study, both methods are used in stainless steel AISI 316L. The purpose of this study is to analyze the effect of sandblasting on the changes in microstructure and the hardness of stainless steel AISI 316L and the combination effect of sandblasting and electropolishing to surface roughness, hardness, and corrosion resistance in stainless steel AISI 316L. Surface roughness of specimens were tested before and after the sandblasting and the electropolishing process. The tool used was sandblasting machine with a working pressure of 5-7 kg/cm2 with a duration of 10 minutes. The sand used was silica sand with a size of 500-800 Î¼m. The tools used in the electropolishing process is the DC power supply with a maximum output of 2x100A. Anode and cathode material was stainless steel AISI 316L. Electrolyte solution consisted of 96% mass fraction of sulfuric acid (H2SO4) and 85% mass fraction of phosphoric acid (H3PO4) with a ratio of 1:1. The parameters used in the electropolish process was voltage of electrical, distance of electrodes and duration of electropolishing process. The results show that increasing the voltage, decreasing the distance, and increasing the duration in the process of electropolishing decrease the surface roughness up to more than 28 times, increase the hardness up to 69% and corrosion resistance up to 37%.